Two Common MTHFR Gene Polymorphisms (C677T and A1298C) and Fetal Congenital Heart Disease Risk: An Updated Meta-Analysis with Trial Sequential Analysis - Zhang, Rui; Huo, Caihong; Wang, Xingning; Dang, Bo; Mu, Yaning; Wang, Yuying (Cellular physiology and biochemistry, 2018)
Abstract Background/Aims: Published studies indicated that the MTHFR gene polymorphisms C677T and A1298C are associated with congenital heart disease (CHD) risk in children, but obtained inconsistent results. Our study aims to reach a more accurate association between these two polymorphisms and CHD risk. Methods: Eligible studies were obtained by screening the PubMed, Embase, China National Knowledge Infrastructure, Wan Fang and VIP databases based on designed searching strategy. The odds ratio (OR) and 95% confidence interval (CI) were calculated. Moreover, a trial sequential analysis was introduced to confirm the positive results and an RNA secondary structure analysis was also applied to discover the potential molecular mechanism. Results: Based on thirty-two published articles, involving 6988 congenital heart disease subjects and 7579 healthy controls, the pooled results from the C677T polymorphism in the fetal population showed increased risks in allelic model (OR=1.32, 95%CI=1.14-1.53), recessive model (OR=1.69, 95%CI=1.25-2.30), dominant model (OR=1.35, 95%CI=1.11-1.64), heterozygote model (OR=1.20, 95%CI=1.01-1.41) and homozygote model (OR=1.75, 95%CI=1.31-2.33). An increased risk was only detected in the A1298C polymorphism in the overall fetal popalation in a recessive model (OR=1.42, 95%CI=1.10-1.84). In the subgroup stratified by region, sample size, genotyping method and source of controls, the increased risks were widely observed in both the C677T and A1298C polymorphisms with CHD risk. Furthermore, trial sequential analysis confirmed our positive results, and the RNA secondary structure analysis detected the changes in the RNA secondary structure caused by the mutant 677T allele and 1298C allele. Conclusion: In summary, we found that the MTHFR C677T polymorphism is associated with a significant increased risk in congenital heart disease in the fetal population. Moreover, an increased risk in the CC genotype of MTHFR A1298C polymorphism was observed, but the protective role of the 1298C allele needs further study.